2018
DOI: 10.1016/j.isci.2018.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Remodeling BAF155 Subunit Regulates the Genesis of Basal Progenitors in Developing Cortex

Abstract: SummaryThe abundance of basal progenitors (BPs), basal radial glia progenitors (bRGs) and basal intermediate progenitors (bIPs), in primate brain has been correlated to the high degree of cortical folding. Here we examined the role of BAF155, a subunit of the chromatin remodeling BAF complex, in generation of cortical progenitor heterogeneity. The conditional deletion of BAF155 led to diminished bIP pool and increased number of bRGs, due to delamination of apical RGs. We found that BAF155 is required for norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 62 publications
5
56
0
Order By: Relevance
“…Shh activation in the mouse via the Gpr161 conditional KO also induced heterotopias that are accompanied with “bRG-like” cell amplification (Shimada et al, 2019). Furthermore, Pax6 loss of function in the small eye mouse mutant also displays basally located progenitors that carry RG characteristics, which is consistent with the results obtained in the Pax6 conditional mutants (Götz et al, 1998; Narayanan et al, 2018). Other mutations have also been shown to be associated with the presence of ectopically located progenitors (reviewed by Bizzotto and Francis, 2015) such as Arl13b and Marcks mouse mutants, potentially showing subtle differences from bRG-like cells.…”
Section: Brgs and Pathologysupporting
confidence: 89%
See 1 more Smart Citation
“…Shh activation in the mouse via the Gpr161 conditional KO also induced heterotopias that are accompanied with “bRG-like” cell amplification (Shimada et al, 2019). Furthermore, Pax6 loss of function in the small eye mouse mutant also displays basally located progenitors that carry RG characteristics, which is consistent with the results obtained in the Pax6 conditional mutants (Götz et al, 1998; Narayanan et al, 2018). Other mutations have also been shown to be associated with the presence of ectopically located progenitors (reviewed by Bizzotto and Francis, 2015) such as Arl13b and Marcks mouse mutants, potentially showing subtle differences from bRG-like cells.…”
Section: Brgs and Pathologysupporting
confidence: 89%
“…This suggests that epigenetic markers, regulated partly by the BAF complex, play a crucial role during several processes of cortical development (Narayanan et al, 2015; Nguyen et al, 2016). In a follow-up study, a Baf155 conditional KO (obtained by crossing Baf155 fl/fl with Emx1-Cre mice) led to an overall decrease of Tbr2+ cells, but also among the remaining Tbr2+ cells, the presence of ectopic IPs in the IZ (Narayanan et al, 2018). The total proportion of Pax6+ cells was not affected, yet ectopic Pax6+/pVim+ cells that resembled bRG-like cells were observed in the IZ, suggesting a delamination of aRGs or bRG-like cell generation.…”
Section: Molecular Mechanisms Associated With the Generation And Amplmentioning
confidence: 99%
“…Recently, a role for adhesion junction belt downregulation at the VZ surface during basal progenitor delamination (Tavano et al, 2018) was shown to be facilitated by Plekha7, a paralog of Plekhg6, which also exhibits differential isoform expression. Furthermore, non-cell autonomous basal progenitor expansion was also recently reported upon knockdown of the chromatin remodeling factor BAF155 (Narayanan et al, 2018). Thus, although the exact underlying mechanism resulting in basal progenitor expansion after PLEKHG6_4 overexpression has yet to be fully elucidated, a wider role for this family of proteins and the non-cell autonomous features associated with such events in cortical neurogenesis may be emerging.…”
Section: Plekhg6 Influences Vz Integritymentioning
confidence: 95%
“…We hence focused on bRG-like cell production at mid-corticogenesis in Lis1 HET mouse mutants. bRG producing mechanisms have been associated with either alterations of mitosis spindle orientation leading to more oblique and vertical divisions (Kalebic et al, 2018; Liu et al, 2017; Wang et al, 2016; Wong et al, 2015), and/or to detachment from the apical surface via decreased cell adhesion (Ju et al, 2016; Martínez-Martínez et al, 2016; Narayanan et al, 2018; Tavano et al, 2018; Taverna et al, 2014). Many of the genes that were described to increase bRG-like cell generation induce more oblique divisions (Penisson et al, 2019), and mitotic spindle orientation is a well-described mechanism that may contribute to the fine tuning of aRG daughter cell fate (LaMonica et al, 2013; Taverna et al, 2014).…”
Section: Discussionmentioning
confidence: 99%